1992
DOI: 10.1152/jappl.1992.72.2.492
|View full text |Cite
|
Sign up to set email alerts
|

Compounds that increase cAMP prevent ischemia-reperfusion pulmonary capillary injury

Abstract: This study evaluated the physiological effects of compounds that increase adenosine 3',5'-cyclic monophosphate (cAMP) on changes in pulmonary capillary permeability and vascular resistance induced by ischemia-reperfusion (I-R) in isolated blood-perfused rabbit lungs. cAMP was elevated by 1) beta-adrenergic stimulation with isoproterenol (ISO, 10(-5) M), 2) post-beta-receptor stimulation of adenylate cyclase with forskolin (FSK, 10(-5) M), 3) and dibutyryl cAMP (DBcAMP, 1 mM), a cAMP analogue. Vascular permeabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 0 publications
5
33
2
Order By: Relevance
“…In these prior studies PDE4 inhibition reduced or prevented the permeability increase that was caused by various mediators of lung injury (Adkins et al, 1992;Moore et al, 1998;Seibert et al, 1992). Part of the difference among these prior studies and our present results relates to the cell type studied.…”
Section: Journal Of Cell Science 121 (1)contrasting
confidence: 77%
“…In these prior studies PDE4 inhibition reduced or prevented the permeability increase that was caused by various mediators of lung injury (Adkins et al, 1992;Moore et al, 1998;Seibert et al, 1992). Part of the difference among these prior studies and our present results relates to the cell type studied.…”
Section: Journal Of Cell Science 121 (1)contrasting
confidence: 77%
“…This condition and the observed leakiness of lymphatic microvessels in vivo (Zweifach and Prather, 1975) are consistent with our finding that low concentrations of db-cAMP correlates with a leaky LEC barrier. Interventions that increase circulating concentrations of cAMP, such as the vascular introduction of rolipram or forskolin for treatment of ischemia-reperfusion injury, are believed to attenuate edema through improved barrier function of blood microvessels (Adkins et al, 1992;Barnard et al, 1994;Seibert et al, 1992). If the trends implied by our in vitro study are present in vivo, then these therapies may have an unintended secondary effect of enhancing the barrier of surrounding lymphatics, with the potential to impede lymphatic drainage.…”
Section: Discussionmentioning
confidence: 94%
“…The cAMP-dependent protein kinase (PKA) has significant and profound protective actions against increases in endothelial permeability. We and others (4,10,32,42,43) have shown that the ubiquitous cellular messenger cAMP prevents increases in endothelial permeability in response to a wide range of inflammatory mediators, including oxidants. Although growing evidence indicates that cAMP activates both PKA-dependent and -independent actions (8,11,26), our recent observations show that protective actions of cAMP against barrier dysfunction are likely mediated predominantly through PKA-dependent signaling mechanisms (32,43).…”
mentioning
confidence: 86%